2014
DOI: 10.3892/mmr.2014.2861
|View full text |Cite
|
Sign up to set email alerts
|

Effect of immunosuppression on the human mesangial cell cycle

Abstract: The present study investigated the effects of immunosuppressive agents [tacrolimus (Tac), cyclosporine A (CsA), mycophenolic acid (MMF) and methylprednisone (MP)] on the proliferation, cell cycle progression and apoptotic rate of human mesangial cells. Cultured human mesangial cells were treated with several concentrations of the immunosuppressive agents for 24, 48 or 72 h. Cell cycle progression, proliferation and apoptosis were analyzed using an MTT assay and flow cytometry. Tac and CsA significantly inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Several studies suggested that the overzealous immune responses associated with macrophage activation syndrome (MAS) or cytokine storm, also known as secondary haemophagocytic lymphohistocytosis (sHLH), may be driving COVID-19 related ARDS [ [3] , [4] , [5] ]. Although several immunosuppressants have been found, most of them have side effects, such as cyclosporine, Tacrolimus [ 6 ], methylprednisone [ 7 ], etc. Therefore, it is crucial to find a natural immunosuppressive agent.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggested that the overzealous immune responses associated with macrophage activation syndrome (MAS) or cytokine storm, also known as secondary haemophagocytic lymphohistocytosis (sHLH), may be driving COVID-19 related ARDS [ [3] , [4] , [5] ]. Although several immunosuppressants have been found, most of them have side effects, such as cyclosporine, Tacrolimus [ 6 ], methylprednisone [ 7 ], etc. Therefore, it is crucial to find a natural immunosuppressive agent.…”
Section: Introductionmentioning
confidence: 99%
“…These breaks have been suggested to arise from SSB during DNA replication and were suggested to result from a general inability to repair DSBs (Zhang et al 2006). Specific CsA responses at the phosphoproteome level include the down-regulation of pathways that control hematopoietic differentiation and immunity (Granzyme B, ErbB2, NGF, Rho GTPase, AML) being consistent with known effects of CsA as an immunosuppressant (Zhou et al 2015) and inducer of apoptosis (Koppelstaetter et al 2018). Differential phosphorylation responses of DNA damage response-related proteins.…”
Section: Discussionmentioning
confidence: 79%
“…In sharp contrast with the effect of Shk and clofazimine on cell cycle progression, the mitochondriotropic Kv1.3 inhibitors slightly increased proliferation when used at low concentrations, as indicated by the increase and decrease of the percentage of cells in S phase and G0/G1 phase, respectively. On the other hand, the same drugs seems to block proliferation of Colo357 cells, by preventing progression from S phase to the G2/M phase ( 44 ). Although knock-down of VDAC1 was shown to reduce proliferation in HeLa cells ( 45 ), for the major part of mitochondrial ion channels, their possible involvement in the regulation of cell cycle progression has not been addressed, to our best knowledge.…”
Section: Discussionmentioning
confidence: 99%